Transparent conducting oxides for electrode applications in light emitting and absorbing devices - Liu, Huiyong; Avrutin, V.; Izyumskaya, N.; Özgür, Ü.; Morkoç, H. (Superlattices and microstructures, 2010)
In both light emitting devices such as light emitting diodes (LEDs), and light absorbing devices such as solar cells (also photodetectors), which are gaining considerable interest for their energy saving and energy production capability, respectively, a compromise must be struck between the need to increase the light emitting/absorbing area/potential and the need for low series resistance of the metal contact grid. This undesirable compromise can be mitigated by using transparent conducting oxides (TCOs), which heretofore have been dominated by ITO (indium tin oxide—an In-rich alloy of indium oxide and tin oxide). Due to the expected scarcity of Indium used in ITO, efforts are underway to develop indium-free TCOs for the above-mentioned devices as well as flat panel displays. ZnO heavily doped with Ga or Al (GZO or AZO) is becoming a very attractive candidate for future generation TCOs. GZO and AZO as well as multilayer TCOs consisting of two TCO layers with a thin metal layer in between have been widely investigated for LEDs and solar cells to enhance device performance. This article succinctly reviews the latest developments in and properties of TCOs, particularly in relation to thin film transparent electrode applications for LEDs and solar cells. Pertinent critical issues and possible solutions are provided as well.